Pancasila sebagai Pokok Pangkal Sudut Pandang Bagi Ilmu Menurut Notonagoro - Ali Mudhofir (Jurnal Filsafat, 2017)
According to Notonagoro, everything came from matter and spirit. All phenomena in the universe have material and final cause. Everything, including sciences, has deity background. Sciences base on reason, willing, intuition, inspiration, and revelation. Both speculative and empirical thought with their variation base on the causal law, in order to take their useful for human life, without depend the truth and reality on usefulness for life. In scientific developing, Pancasila, therefore, is a guideline for sciences— humanities, social and natural sciences. Research and sciences developing in Indonesia ought to be based on and spirited by Pancasila. It is very important for national education generally and specially for high education according to the guideline of 1945 National Constitution. As a basis of scientific point of view, Pancasila allow for scientists do not to adopt the position of science for the sake of science; but teleological, namely, they ought to priority the sciences for good life. Moreover, they ought to care of the direct and pure task of sciences, namely, in order to get truth and reality.